A Review of Beneficial Low-Intensity Exercises in Diabetic Peripheral Neuropathy Patients - Carley E Johnson; Jody K Takemoto (Frontiers Media S.A., 2019)
The American Diabetic Association standards of medical care for diabetic patients recommends moderate intensity exercise to help manage diabetes; however, this recommendation may be unmanageable for patients who have become inactive or unable to reach this intensity. The purpose of this review is to determine if low-intensity exercises demonstrate improvement in diabetic peripheral neuropathy symptoms in order to utilize these exercises as a starting point for inactive patients. Studies in low-intensity exercises from 2013 to May 2018 were systematically searched in PubMed, SCOPUS, and Cochrane Library databases. The studies in this research have shown that low-intensity resistance exercises have promising outcomes such as improvements in pain interference with daily activities, pain thresholds, and reductions in neuropathy symptoms. Low-intensity aerobic therapy adds to the quality of life of the patient, and increases in strength of the lower limbs show an improvement in foot sensation and a reduction in pain and tingling symptoms.